Cow comfort through the transition period - Smith, John F., 1962-; Harner, Joseph P.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Managing transition cows is a significant problem on dairy farms. The issues include nutritional considerations, stocking rates, metabolic disorders, heat stress, and access to feed and water. Often management of transition cows is limited to nutritional considerations. Facilities, grouping strategies, stocking rates, heat stress, and access to feed and water also have a dramatic impact on milk production, herd health, culling rates, and reproductive efficiency. Often nutritional benefits can be negated by not managing cow comfort issues. Producers can improve profitability by managing those variables.
Keywords: Dairy; Housing; Transition cows; Comfort